2010
DOI: 10.1007/s11101-010-9183-z
|View full text |Cite
|
Sign up to set email alerts
|

Saponins as cytotoxic agents: a review

Abstract: Saponins are natural glycosides which possess a wide range of pharmacological properties including cytotoxic activity. In this review, the recent studies (2005–2009) concerning the cytotoxic activity of saponins have been summarized. The correlations between the structure and the cytotoxicity of both steroid and triterpenoid saponins have been described as well as the most common mechanisms of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
394
0
18

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 611 publications
(427 citation statements)
references
References 142 publications
(202 reference statements)
15
394
0
18
Order By: Relevance
“…Saponins are a diverse group of secondary metabolites characterized by a structure containing a triterpene or steroid aglycone called sapogenin and one or more sugar chains (Güçlü-Üstündağ and Mazza, 2007;Podolak et al, 2010), which have already been identified in more than 100 plant families. The consumption of saponin-containing plant foods may be associated with beneficial and adverse effects.…”
Section: Saponinsmentioning
confidence: 99%
See 3 more Smart Citations
“…Saponins are a diverse group of secondary metabolites characterized by a structure containing a triterpene or steroid aglycone called sapogenin and one or more sugar chains (Güçlü-Üstündağ and Mazza, 2007;Podolak et al, 2010), which have already been identified in more than 100 plant families. The consumption of saponin-containing plant foods may be associated with beneficial and adverse effects.…”
Section: Saponinsmentioning
confidence: 99%
“…All legumes have triterpene-type saponins (Muzquiz et al, 2012). In fact, while triterpenoid saponins are mainly found in Magnoliopsida (former dicotyledons), steroidal saponins are more abundant in Liliopsida (former Gry et al (2006), Hylands and Mansour (1982), Hylands and Salama (1976), Oobayashi et al (1992), Pohlmann (1975 monocotyledons) (Güçlü-Üstündağ and Mazza, 2007;Podolak et al, 2010). The structural complexity of these compounds results in a wide range of biological properties (Güçlü-Üstündağ and Mazza, 2007) among which in vitro haemolytic activity has been one of the most investigated ones.…”
Section: Saponinsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Most of them are currently investigated for their antitumor activity. 10,11 Extensive studies on the relationship between saponin structure and activity, described and summarized in a recent review, 10 confirm that the biological activity of saponins is influenced both by the aglycone and the sugar mojeties in the molecule. The cytotoxic action of saponins is likely to result from their ability to form complexes with the cell membrane cholesterol, leading to pore formation and cell permeabilization.…”
Section: Role Of Metallothionein and Nitric Oxide In The Cell Responsmentioning
confidence: 96%